2015
DOI: 10.1002/mrm.25687
|View full text |Cite
|
Sign up to set email alerts
|

Numerical prediction of temperature elevation induced around metallic hip prostheses by traditional, split, and uniplanar gradient coils

Abstract: Purpose The paper presents a computational study for the estimation of the temperature elevation occurring in a human subject carrying metallic hip prostheses when exposed to the magnetic field produced by gradient coils. Methods The simulations are performed through validated numerical codes, which solve the electromagnetic and thermal equations applied to a high‐resolution anatomical human model. Three different sets of gradient coils (traditional, split and uniplanar) are considered to evaluate the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…Applying, for comparison, the product echo planar imaging sequence, we obtained 40%, with Graf's sequence and implant position 2.6% of this value. The resulting tissue temperatures can only be determined by simulations that take into account heat dissipation, such as by perfusion , whereas here an independent experimental test of such simulations is intended. An RF heating test performed for comparison (http://onlinelibrary.wiley.com/store/10.1002/mrm.26652/asset/supinfo/mrm26652-sup-0001-suppfigs.pdf?v=1&s=9755943faffb22e5b22e520009512daf37a90d6d) showed no detectable temperature effect.…”
mentioning
confidence: 99%
“…Applying, for comparison, the product echo planar imaging sequence, we obtained 40%, with Graf's sequence and implant position 2.6% of this value. The resulting tissue temperatures can only be determined by simulations that take into account heat dissipation, such as by perfusion , whereas here an independent experimental test of such simulations is intended. An RF heating test performed for comparison (http://onlinelibrary.wiley.com/store/10.1002/mrm.26652/asset/supinfo/mrm26652-sup-0001-suppfigs.pdf?v=1&s=9755943faffb22e5b22e520009512daf37a90d6d) showed no detectable temperature effect.…”
mentioning
confidence: 99%
“…Body RF coil transmission induces RF power deposition in a large volume including body regions far away from the ROI. This is of clinical relevance for cardiac patients with hip replacement prosthesis (clinical prevalence in an older population of up to 5% [41]) and other abdominal or peripheral implants (for example vena cava filter, clinical prevalence in an older population of up to 4% [42]) which constitute an RF-heating related contraindication if body RF coil transmission is used [43]. Local transmit RF coils dedicated for CMR restrict power deposition primarily to the upper chest and hence permit inclusion of these patients into CMR examinations.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper , we showed that the tissues surrounding a metallic hip prosthesis exposed to a gradient field (GF) may undergo a nonnegligible heating (up to some degree), as a result of the electromagnetic energy deposited in the implant. Since then, we have realized that in the MR community these results are generally received with some skepticism, probably because of the fact that most of the scientific papers dealing with thermal problems in MRI focus on RF fields .…”
Section: Total Joule Losses P (In Watt) Developed Within the Spherementioning
confidence: 99%